Pom1p, a fission yeast protein kinase that provides positional information for both polarized growth and cytokinesis - Bähler, Jürg (Cold Spring Harbor Laboratory Press, 1998)
Schizosaccharomyces pombe cells have a well-defined pattern of polarized growth at the cell ends during interphase and divide symmetrically into two equal-sized daughter cells. We identified a gene, pom1, that provides positional information for both growth and division in S. pombe. pom1 mutants form functioning growth zones and division septa but show several abnormalities: (1) After division, cells initiate growth with equal frequencies from either the old or the new end; (2) most cells never switch to bipolar growth but instead grow exclusively at the randomly chosen end; (3) some cells mislocalize their growth axis altogether, leading to the formation of angled and branched cells; and (4) many cells misplace and/or misorient their septa, leading to asymmetric cell division. pom1 encodes a putative protein kinase that is concentrated at the new cell end during interphase, at both cell ends during mitosis, and at the septation site after mitosis. Small amounts of Pom1p are also found at the old cell end during interphase and associated with the actin ring during mitosis. Pom1p localization to the cell ends is independent of actin but requires microtubules and Tea1p. pom1 mutations are synthetically lethal with several other mutations that affect cytokinesis and/or the actin or microtubule cytoskeleton. Thus, Pom1p may position the growth and cytokinesis machineries by interaction with both the actin and microtubule cytoskeletons.